Here is the answer for the question – **Which quadratic equation is equivalent to (x2 – 1)2 – 11(x2 – 1) + 24 = 0?**. You’ll find the correct answer below

### Which quadratic equation is equivalent to (x2 – 1)2 – 11(x2 – 1) + 24 = 0?

**The Correct Answer is**

**u2 – 11u + 24 = 0 where u = (x2 – 1)**

### Reason Explained

u2 – 11u + 24 = 0 where u = (x2 – 1) is correct for Which quadratic equation is equivalent to (x2 – 1)2 – 11(x2 – 1) + 24 = 0?

Thankyou for using answerout. We hope you get all your answers here. If you have any special questions, you can comment to ask us.

Latest posts by Alex Timmons (see all)

- What element of epic poetry is contained in the following passage - March 27, 2023
- The electron’s drift speed in a 1.0mm diameter gold wire is 5.0E-5 m/s. How long does it take 1 mol electrons to flow through a cross section of the wire? - March 26, 2023
- Organic fertilizers made from dried and pulverized manure are: - March 26, 2023